Noise Analysis in VLC Optical Link based Discrette OP-AMP Trans-impedance Amplifier (TIA) - Syifaul Fuada; Trio Adiono; Angga Pratama Putra; Yulian Aska (Universitas Ahmad Dahlan, 2017)
To design Visible Light Communication (VLC) system, there are several requirements that needs to be met. One of the requirements is an active component selection (e.g. Op Amp). As an ideal communication system, VLC system has to be able to provides wide bandwidth access with minimum noise. The Transimpedance amplifiers (TIAs) is one of main components in optical system which is placed in the first stage of receiver system. It is used to convert the current output from photodiode to voltage. We have designed a 1 MHz fGBW TIA with low noise (in μVrms range). This paper aims to explain the design and implementation of TIA circuit with photovoltaic topology which cover empirical calculations and simulation of TIA’s bandwidth and its noise sources, i.e. resistor feedback noise, current noise, voltage noise and total noise based on RSS. The OP-AMP is chosen from Texas Instruments product, OPA 380, and photodiode is chosen from OSRAM, SFH213, then simulated by TINA-TI SPICE® software. The noise in TIA circuit is analyzed clearly. The developed kit is ready to be implemented in VLC system.